Mitigating the dead-time effects on harmonics spectrum of inverter waveform by the confined band VSFPWM technique - Hussain Attia; Hang Seng Che; Tan Kheng Suan Freddy; Ahmad Elkhateb (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The dead-time is necessary to be inserted between the gates drive pulses of the two power electronic switches in a one leg of any inverter to avoid a short circuit in the leg and the DC supply as well. However, adding the dead-time increases the low order harmonics of the output voltage/current waveform of the inverter. This paper investigates the positive effects of decreasing the pulse width modulation (PWM) drive pulses number per fundamental period on the current low order harmonics. In addition, this paper evaluates the impact of the confined band variable switching frequency pulse width modulation (CB-VSFPWM) technique on inverter performance in terms of dead-time mitigating, and consequenctely lowering the low order harmonics. CB-VSFPWM technique reduces the total harmonic distortion (THD) levels in the inverter output current as well. Theoretical analysis of the CB-VSFPWM effectiveness in reducing the negative effect of the dead-time has explained in this study and confirmed by the MATLAB/Simulink simulation results.